A review of Palm Oil Mill Effluents (POME) as an alternative fertilizer on oil palm / Mohd Haikal Ismail - Ismail, Mohd Haikal (Faculty of Plantation and Agrotechnology, 2016)
Oil Palm cover has growth in the last decades, the significances improvement in palm oil production resulting escalation level of effluents know as by-product of fresh fruit bunch (FFB) processing. Palm oil mill effluent (POME) is treated as unwanted product because the cost to maintain before discharge to environment is extraordinary expensive. Palm oil mill effluent palm oil mill effluent (POME) contains high solid, oil and grease with thick brownish liquid including, biological oxygen demand (BOD) and chemical oxygen demand (COD). The aim of this review paper is for discovering the potential an alternative fertilizer could be discover form palm oil mill effluent (POME) as a resource that can be benefit to the oil palm industrial. Several treatment technologies created for palm oil mill effluent (POME) treatment, from the time when the straight release of palm oil mill effluent (POME) unpleasantly disturbs the environment. Due to the high availability of total solids in palm oil mill effluent (POME), efforts have been through to alter this waste into valued products such as an organic fertilizer. Even though palm oil mill effluent (POME) is naturally organic, it is quite problematic to decay in natural conditions. Earthworms can digest the palm oil mill effluent (POME) creating valuable products such as vermicompost. Vermicompost is a beneficial product high in nutrients that can be recycled as nourishment in oil palm plantations. This review deliberates several current treatment methods of palm oil mill effluent (POME). Palm oil mill effluent (POME) can be efficiently treated by using alternative method which is recommended as a good sustainable management practice of this waste.